An Assessment of Attitudes and Concerns of Residents towards Educational Scout-Based Tourism in Indonesia - Mufidah Afiyanti; Harsuko Riniwati; Sri Wardhani; Rizha Hardyansah; Ferik Antyo Agus Wibowo (Journal of Indonesian Tourism and Development Studies, 2020)
A rural village, similar to other rural areas, has a need to be economically independent in cope with their sustainable economic growth.  A unique value accompanied by good hospitality has been the main situation concerns with tourism. This paper discusses the assessment of attitudes and concerns of residents in the-only educational scout-based tourism village in Indonesia. Data for the study was collected by spreading the questionnaire directly to residents. Data collected through a direct survey. Attitudes were assessed by a 5-point strongly disagree and strongly agree scale on several questions implying residents' opinions on educational scout-based tourism and its impacts. The results showed great support for tourism. Residents have positive attitudes regarding tourism as they associate it to be important for their economic growth. The main concerns for residents in welcoming tourism are including their village community progress, better services in health and education, as well as the hope for the available market in their crafts products. However, the results also showed residents were not particularly assured of the user (tourists) money circulation and facilities benefit from the tourism activities occurred in their village, even though they support educational scout-based tourism development. It indicated a lack of self-confidence and trust issues towards the tourism manager. In this paper, a slight correlation between education and residents' attitudes towards tourism also discussed.  Keywords: confidence, educational tourism, Lebakharjo, trust.